Massachusetts Application of National Assessment Items in Citizenship and Science - Massachusetts State Dept. of Education, Boston; Massachusetts State Dept. of Education, Boston ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1972)
The 1972 assessment activities in the Massachusetts schools concentrated on the areas of citizenship and science, utilizing two seventh grade samples of 10,000 students each, with each group completing only one assessment form. The testing program utilized National Assessment Items for age 13, as well as a few items from the Measurement Research Center to replace items not released by National Assessment for the objective being measured. The following procedures were carried out: (1) two four-page pamphlets, one for Citizenship and one for Science, were prepared listing the objectives used by National Assessment in these curricula area; (2) a rating scale to indicate priority of objectives was prepared and sent to each of the 57 schools used in the sample population; rating categories applied by each school to each objective were: (a) objective with highest priority; (b) objective of importance requiring extensive evaluation; (c) objective important, but not requiring extensive evaluation; (d) objective not of importance; omission will have no effect; and (e) objective not applicable to this school system. Objective results of the assessment were not available for inclusion. Attachment A to the report provides samples of the Citizenship and Science Objectives, and Attachment B is a summary of the ratings of all Science Objectives and identifies the number of items to be used in measuring each objective. (DB)
Educational level discussed: Grade 7.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Citizenship; Criterion Referenced Tests; Grade 7.; Measurement Techniques; National Competency Tests; Objective Tests; Rating Scales; Science Tests; State Programs; Testing Programs; Massachusetts